FUNCTIONAL STATE OF THE PINEAL GLAND IN WOMEN WITH THREATENED ABORTION IN THE FIRST TRIMESTER - FURTHER PROSPECTS OF PREGNANCY - А. Пушкашу (Bukovynian State Medical University, 2023)
Melatonin is an important hormone for normal pregnancy development, but the infl uence of serotonin remains poorly understood. Low melatonin production can lead to spontaneous abortion by stimulating progesterone secretion and inhibiting prostaglandin synthesis. Melatonin has an eff ect on the induction and blocking of apoptosis of the villous cytotrophoblast and promotes the development of the syncytiotrophoblast. Analysis of the frequency of positive pregnancy showed a signifi cant impact on the course of pregnancy and childbirth, compliance with sleep and rest also contribute to a positive eff ect, but there is no general concept, which makes the subject relevant. The aim of the study. To evaluate the functional state of the pineal gland, in particular, the amount of melatonin and serotonin in the blood of pregnant women at 10-12 weeks of gestation with a threat of abortion, which was manifested by bloody discharge or formation of retrochorionic hematoma, and the consequences of pregnancy. Materials and methods. Two groups were formed: I main group - 40 pregnant women with a threat of abortion and formation of retrochorionic hematoma, II control group - 44 healthy pregnant women. Obstetric examination, enzyme- linked immunosorbent assay for determination of melatonin, serotonin, chorionic gonadotropin, and ultrasound were performed. Informed consent of pregnant women was obtained with adequate explanation of the purpose, objectives, methods and scope of laboratory and instrumental research methods. The study protocol was approved by the Commission on Biomedical Ethics of the Bukovinian State Medical University, 2015 (minutes of the Commission meeting No 2 from the 19.10.2023 year). The study was conducted in accordance with the basic provisions of GCP (1996), the Convention of the Council of Europe on Human Rights and Biomedicine (April 4, 1997), the Declaration of Helsinki of the World Medical Association for the Ethical Principles of Scientifi c Medical Research Involving Human Subjects (1964-2008), the Order of the Ministry of Health of Ukraine 690 of September 23, 2009 (as amended by the Order of the Ministry of Health of Ukraine 523 of July 12, 2012). Statistical analysis was performed using generally accepted methods of variance statistics. Reliability was assessed by Student's t-test. Diff erences were considered signifi cant if the signifi cance level was p≤0.05. We also performed correlation analysis in Microsoft Excel, using the method of squares (Pearson's method) to determine the correlation coeffi cient. The work is a fragment of the research work of the Department of Obstetrics and Gynecology, UDC 618.1-053.34 + 618.1-0536 /.8]. -07-084-08 «Prevention, diagnosis and treatment of disorders of the perinatal period and reproductive system of women and adolescent girls» (No. 201110Н, state registration number 0111U006499. The term of implementation is 02.2011-12.2015). Results of the study. According to the obtained results, retrochorionic hematoma up to 1 cm is detected three times more often than over 1 cm, while the level of melatonin is not signifi cantly lower, but with retrochorionic hematoma over 1 cm a signifi cant decrease is observed in cases of further normal pregnancy and childbirth. With further complications of pregnancy in retrochoroidal hematoma up to 1 cm, there is a signifi cant signifi cant decrease in melatonin (p ˂ 0.001), in contrast to retrochoroidal hematoma over 1 cm, where no signifi cant diff erence was found in the complicated course of pregnancy (p > 0.05). Serotonin levels were elevated in all subgroups regardless of hematoma size and subsequent pregnancy outcome.  Conclusions. In case of threatened abortion in the fi rst trimester with formation of retrochorionic hematoma, the risk of complicated pregnancy remains in 60.87 % of cases. Determination of pineal hormones revealed a signifi cant increase in serotonin with a simultaneous signifi cant decrease in melatonin, while maintaining a positive relationship between the hormones, indicating a disruption of melatonin synthesis in the central nervous system. This is confi rmed by the normal level of chorionic gonadotropin and the preservation of embryonic viability. Since the disruption of hormone formation in the pineal gland has been established, adherence to the recommendations for adequate rest may positively aff ect the further outcome of pregnancy and childbirth.